Neuro-ophthalmologic Outcomes of Orbital Apex Syndrome Caused by Invasive Fungal Rhinosinusitis - Park, Minhae; Shin, Joongbo; Lee, Eunkyu; Ryu, Gwanghui; Kang, Min Chae; Park, Kyung-Ah; Kong, Doo-Sik; Huh, Kyungmin; Kim, Kyunga; Kim, Hyo-Yeol; Jung, Yong Gi; Hong, Sang Duk (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives Orbital apex syndrome (OAS) is characterized by visual loss, ophthalmoplegia, ptosis, and orbital pain. This study aims to analyze neuro-ophthalmologic outcomes of OAS resulting from invasive fungal rhinosinusitis (IFS).Methods This retrospective study analyzed 25 patients diagnosed with OAS resulting from IFS between January 2018 and July 2022. Patient's visual acuity, degree of ophthalmoplegia, ptosis, and orbital pain were analyzed. Poor and nonpoor visual acuity were classified based on 20/200. The study also investigated risk factors for the failure of vision restoration.Results Only 1 of 25 patients died from the progression of IFS. Among the 25 patients, 5 (20%) had initial visual acuity better than 20/200 before treatment and 20 (80%) had worse vision than 20/200. Four (80%) of five patients with better than 20/200 maintained visual acuity. Four (20%) of 20 patients with worse than 20/200 recovered to better than 20/200 but others remained or declined to worse vision after treatment. The presence of an infiltrative lesion in cavernous sinus on magnetic resonance image scans was significant in univariate but not multivariate analysis (odds ratio, 24.39; 95% confidence interval, 1.543–333.333; P-value = 0.023). Among the patients with worse than 20/200 vision, the patients whose treatment started less than 4 weeks achieved 33.3% (4/12 patients) vision recovery. In contrast, ophthalmoplegia, ptosis, and pain recovered more successfully than vision.Conclusion Although OAS caused by IFS has been reported as very rare, early pathological diagnosis and appropriate treatment can result in good survival and favorable neuro-ophthalmologic outcomes.
Keywords: invasive fungal sinusitis; computed tomography; endoscopic sinus surgery; fungal sinusitis; imaging